Assessing stress conditions and impact velocities in fluidized bed opposed jet mills - Strobel, Alexander; Köninger, Benedikt; Romeis, Stefan; Schott, Florian; Wirth, Karl Ernst; Peukert, Wolfgang (Particuology, 2020)
Fluidized bed opposed jet mills are capable of meeting the continuously growing demand for contamination-free fine particles. In this type of jet mill, the solid material is entrained and accelerated by expanding gas jets that are focused onto a focal point inside a fluidized bed. The resulting particle collisions induce breakage. The process is affected by the relative particle velocities and the number of particle–particle collisions. Clearly, both quantities are distributed. However, to date, neither relative particle velocities nor collision frequencies in such units have been determined. The present work introduces an innovative method to assess the stressing conditions in jet mills experimentally. To this end, mixtures of glass and ductile metal microspheres were used, with the latter employed in small amounts. Inter-particle collisions between the aluminum and glass spheres lead to the formation of dents on the microparticles. The size and number of these dents are associated with the individual collision velocities and overall collision frequencies. The correlation between dent size and collision velocity was obtained from finite element calculations based on empirical data. The proposed approach was validated using particle image velocimetry during secondary gas injection into a fluidized bed reactor. In this case the effect of the distance between two opposed nozzles was examined. For a lab-scaled fluidized bed opposed jet mill the effects of gas pressure and hold-up were investigated. Relative particle velocities were found to be significantly lower than the gas velocities, while the number of contacts per particle was determined to be extremely high.
CRIS-Team Scopus Importer:2020-07-03
Keywords: Finite element modeling; Fluidized bed opposed jet mill; Relative velocity distribution; Single particle probes; Stress number distribution

Classifier performance during dynamic fine grinding in fluidized bed opposed jet mills - Köninger, Benedikt; Spoetter, Christian; Romeis, Stefan; Weber, Alfred P.; Wirth, Karl-Ernst (Advanced Powder Technology, 2019)
Dry grinding of particles to sizes below 10 µm can be realized in fluidized bed opposed jet mills. In these mills the energy for comminution is supplied by pressurized gas, which is introduced through focused nozzles. The gas transports the material towards an internal classifier, which separates the fines from the coarse material. The fines are discharged whereas the coarse material is recycled. Within this study special attention is paid to separation at the classifying wheel. Limestone batch grinding experiments were performed in a fluidized bed opposed jet mill equipped with on-line and in-line probes: The particle size distributions (PSDs) of the product flow and the solid concentration below the classifier were determined on-line. The flow field around the classifier was recorded by a high-speed camera and off-line measurements of the mill inventory and its PSD were performed. Our measurements reveal that the solid transport from the milling zone to the classifier and the classifier performance strongly depend on solid concentration. Increasing the solid feed concentration or the classifier wheel speed leads to unwanted accumulation of product-sized particles inside the mill. In particular, we find high solid loadings of up to 1.05 g⋅g−1 and strong cluster formation (local zones of high solid concentration) in the vicinity of the classifier blades. Estimated separation efficiency curves of the classifier show a strong “fish-hook effect” which increases with the solid concentration. Our findings are relevant for future process optimization by careful tuning of grinding performance, holdup and classifier speed.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Classification; Fluidized bed opposed jet mill; High-speed imaging; Internal separation curve; Process dynamics

Dynamics of fine grinding in a fluidized bed opposed jet mill - Köninger, Benedikt; Hensler, Timo; Romeis, Stefan; Peukert, Wolfgang; Wirth, Karl-Ernst (Powder Technology, 2018)
Keywords: Fine dry comminution; First order kinetics; Fluidized bed opposed jet mill; Process dynamics

Horizontal secondary gas injection in fluidized beds: Solid concentration and velocity in multiphase jets - Köninger, Benedikt; Hensler, Timo; Schug, Sebastian; Arlt, Wolfgang; Wirth, Karl-Ernst (Powder Technology, 2017)

Impact comminution in jet mills - Strobel, Alexander; Köninger, Benedikt; Romeis, Stefan; Wirth, Karl Ernst; Peukert, Wolfgang (Dynamic Flowsheet Simulation of Solids Processes, 2020)
Modelling the comminution in jet mills with respect to the complex twophase flow and the dynamic process behaviour is still a challenging task. The processed solids pass through several stages in the mill: The comminution process in the lower part, the pneumatic transport towards the classifier in the middle section, and the classification step at the top. In this contribution, the grinding kinetics and process behaviour during quasi-batch and fed-batch operational mode for different holdups, classifier speeds, and particle sizes are examined in detail. A previously developed method using well-characterized aluminium particle probes to access the stressing conditions is adapted for application in the investigated jet mill: The relative particle impact velocity is linked to the geometric changes of the particles upon impact. A high number of impact events happen in the mill, while at the same time, the average particle velocity is comparatively low. Besides the stressing conditions, breakage probabilities for the used glass beads are determined by single particle impact experiments and described by the model of Vogel and Peukert. Solids concentration measurements and high-speed imaging reveal the formation of particle clusters at the classifier and its periphery. These clusters have a massive impact on the classification step itself: Fine particles are trapped inside the clusters and are not discharged. Based on an adaption of the breakage model, and using the mean relative particle impact velocity determined by the particle probes, a model for the product mass flow is introduced.
CRIS-Team Scopus Importer:2020-08-28

Prallzerkleinerung in Fließbettgegenstrahlmühlen: Vom Einzelkorn zur Mühle - Romeis, Stefan; Köninger, Benedikt; Strobel, Alexander; Wirth, Karl-Ernst; Peukert, Wolfgang (Chemie Ingenieur Technik, 2016)
Keywords: zerkleinerung; prallmühle; partikel

Solid distribution in fluidized and fixed beds with horizontal high speed gas jets - Köninger, Benedikt; Koegl, Thilo; Hensler, Timo; Arlt, Wolfgang; Wirth, Karl-Ernst (Powder Technology, 2018)
High speed jet penetration in fluidized beds can be used for particle size control or comminution processes. Thus, particle breakage is determined by the kinetic energy of the solids and the frequency of particle-particle impacts inside the flow. Both aspects are influenced by the solid concentration inside the jets and at the boundary. For understanding the fundamental breakage mechanism, the determination of the solid distribution in those complex flows is an important contribution. In order to access the turbulent and delicate multiphase flow, a modern fast X-ray computed tomography unit was used in this work. To obtain quantitative solid concentrations, the measurement system was optimized by means of hardware filtering, exposure time and reconstruction algorithm. These methods allowed the investigation of influencing parameters like jet velocity, fluidization velocity or particle size on the solid distribution in a single jet. With the obtained experimental data, correlations for the axial and radial solid distribution were developed. In addition, the influence of multiple jet injection with a common focal point is presented.
Keywords: Horizontal secondary gas injection; Jet milling; X-ray computed tomography; Solid distribution; Visualization of flow pattern

Temperature characteristics in a flash atomization process - Günther, Astrid; Bräuer, Andreas; Siegler, Philipp; Köninger, Benedikt; Wirth, Karl-Ernst (Atomization and Sprays, 2016)